Hormonal status in progressive myopic Chorioretinitis (Texas Journal of Multidisciplinary Studies, 2022)
The article explains the scientific significance of retinal dystrophy. An actual problem in ophthalmology at the present time is retinal dystrophy of varying degrees. This is due to the progressive increase in the incidence of this pathology. Until now, a unified theory about the pathogenesis of retinal dystrophy has not been formed. Visually, this is usually not noticeable if we are talking about small degrees of retinal pathology. But what leads to the growth of the eye is a very stormy topic for discussion today, which generates a lot of myths.